2015
DOI: 10.15560/11.1.1523
|View full text |Cite
|
Sign up to set email alerts
|

First record of Chrysopelea taprobanica Smith, 1943 (Squamata: Colubridae) from India

Abstract: Chrysopelea taprobanica Smith, 1943 was previously considered to be endemic to the dry and intermediate zones of Sri Lanka. However, an adult specimen of C. taprobanica was collected from Seshachalam Biosphere Reserve of Andhra Pradesh, India, being the first record of this snake species from India, significantly extending the known range of distribution of the species. The dry zones of peninsular India were connected with Sri Lanka as recently as ca. 17,000 years ago, which probably allowed movement of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Therefore, it is not surprising that this species also occurs on the Indian peninsula. A similar case of another closely related colubrid snake purported as a Sri Lankan endemic, reported authentically from India is Chrysopelea taprobanica Smith, 1943(Guptha et al 2015, Somaweera et al 2015. We also acknowledge the fact that some populations thought to belong to the same species were also later shown to be different at species level between the Western Ghats and Sri Lanka, e.g.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, it is not surprising that this species also occurs on the Indian peninsula. A similar case of another closely related colubrid snake purported as a Sri Lankan endemic, reported authentically from India is Chrysopelea taprobanica Smith, 1943(Guptha et al 2015, Somaweera et al 2015. We also acknowledge the fact that some populations thought to belong to the same species were also later shown to be different at species level between the Western Ghats and Sri Lanka, e.g.…”
Section: Discussionmentioning
confidence: 61%
“…Chrysopelea ornata is a widespread species found across southern and southeastern Asia. Chrysopelea taprobanica initially was thought to be endemic to Sri Lanka (Smith 1943;Taylor 1950), but subsequent studies reported it from the Eastern Ghats of India (Constable 1949;Guptha et al 2015; see also Somaweera et al 2015). Later, Narayanan et al (2017) reported C. cf.…”
mentioning
confidence: 99%